Efektivitas Badan Usaha Milik Desa Di Desa Poly Kecamatan Tinombo Selatan Kabupaten Parigi Moutong - Wangsi, Misna; Mangngasing, Nasir; Samsu, M. Kafrawi Al-kafiah (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the effectiveness of village-owned enterprises in Poly Village, South Tinombo District, Parigi Moutong Regency. This study uses Duncan's theory cited by Richard M Steers (1985: 53) which includes aspects of achieving integration and adaptation goals. This study uses a qualitative approach with descriptive type. Data collection techniques using observation, interviews and documentation. Based on the results of research on the effectiveness of village-owned enterprises in the village of Poly, shows that the management of village-owned enterprises have not been running effectively and optimally. The lack of optimal management can be seen in the aspect of achieving goals, integration and adaptation shows that the programs and business units run by BUMDes have not been evenly felt by the people of Poly village, this is because there is still a lack of budget in the management of BUMDes so that it affects the purpose of BUMDes in adding business units. Integration aspects, at the socialization stage the formation of village business units has indeed been carried out but has not run optimally due to lack of community participation in the socialization process, so that some people do not know about BUMDes and what programs are being run. Adaptation aspect that the implementation of the BUMDes program in Poly Village is in accordance with the potential of the village, the majority of the population are farmers but have not fully utilized the potential of the existing village. Business units such as tunnel rentals, tractors, rice fertilizers, and rice pawns greatly help the community overcome difficulties in meeting their work needs at a more affordable cost. However, there are obstacles in the management and implementation of the program due to lack of knowledge and skills of BUMDes administrators and the community about the importance of BUMDes effectiveness for community welfare and village progress.